Antecedents of Marketing Strategy in Palm Oil Industry Spare Parts Supplier Company (Case Study of PT. Technindo Contromatra) - Pardomuan S, Ernst Tunggul; Tongam Sirait (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
The Palm Oil Industry is one of the important industries that support the Indonesian economy because it brings in a lot of foreign exchange and absorbs a lot of work. One of the parties involved in the supply chain of the palm oil industry is a supplier of equipment and spare parts for palm oil processing mills. The purpose of this paper is to analyze the importance of equipment and spare parts supplier companies to add to using the appropriate marketing mix to develop their company's business. The method used in processing interview data and collecting questionnaire data. The results obtained are inputs in the form of business strategy adjustments for the company.